Evaluation of failure risk for prestressed anchor cables based on the AHP-ideal point method: An engineering application. (August 2022) - Zhu, Hongwei; Xiang, Qin; Luo, Bin; Du, Yixiang; Li, Mingjun
Highlights: A novel analysis model was established for failure risk of the prestressed anchor cable. AHP-ideal point method was first applied for predicting failure risk of the prestressed anchor cable. A hierarchy model of the influence factors for failure risk of the prestressed anchor cable was established. Reasonable agreements were obtained and could provide some advice for further study. Abstract: This research is focused on the evaluation method of failure risk of prestressed anchor cable, and an accurate evaluation method with a simple operation is proposed. The analytic hierarchy process are used to determine the weight of each evaluation element, the closeness degree of each indicator is determined based on ideal point method. The results show the following: (1) the evaluation method better integrates the effects of multiple factors on the failure risk of the prestressed anchor cable, and the evaluation results are accurate and consistent with the actual situation of the project; (2) the evaluation result is intuitive, and the correlation degree obtained can not only reflect the failure risk grade of prestressed anchor cable, but also the possibility of deterioration of the failure risk of the evaluated anchor cable to a higher level could be obtained; and (3) the rationality and practicability is verified by comparison with field situation and other several methods. In addition, this method has good applicability in solving the other uncertain problems.